Wireless control system for spy devices based dual tone multi frequency technology - Jabbar Shatti Jahlool; Mohammed Abdulla Abdulsada (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Obtaining information is one of the most important requirements for  intelligence works, spy surveillance cameras and listening devices are among the important means for this. One problem of using these means is a mechanism of controlling them to sustain their work efficiently for the perpetuating of achieving the purpose of their installation. In this research, the problem of controlling these devices has been overcome, by designing asystem dependent on the dual tone multi frequency (DTMF) and global system for mobile(GSM) networks. In the proposed work, designing and  implementing a system to remotely and wirelessly control of the movement of spy cameras in all directions as well as the ability to control the on/off listing audio device anytime and anywhere. The proposed mechanism is implementedby dividing the work into nine modes, with each one performing one specificfunction. These work modes are used to control all system activities such as control the horizontal directional motor (HDM) to change the spy camera in different horizontal directions, control the vertical directional motor (VDM) to change the camera in vertical directions and control the working status of the listening device.